Entre o litoral sul de Sergipe e o litoral norte da Bahia : onde as políticas territoriais se encontram - Santos, Carla Norma Correia dos (2017)
The municipalities of Indiaroba, locatedon thesoutherncoast of Sergipe, and Jandaíra, on thenorthcoast of Bahia, thedevelopment of tourism and real estateactivity on thelandoccupation by subdivisions for secondresidenceorsummervacation, promoted a territorial andeconomicalreconfiguration. Thesemunicipalities are contiguousand located in extremelimits of theirstateswhichplacedthem in a situation of geographicisolationwithrespect to Aracaju and Salvador. However,therewas a connection betweenthemestablished in geographicalproximity and theirneighbourhood. A stateactionthroughtheconstruction of a road network, transport and communication favored a greater connection between Indiaroba and Jandaíra, and amongnearbymunicipalitiesboth in Sergipe and Bahia, thussettingintraregionaleconomicrelations. From "invisible" territories, thesemunicipalitiesbecomedesirableones, places of high real estatevaluesuch as beaches, dunes, lagoons and estuarieshavebeenmadeattractive to private capital for buildingresidentialcondominiums, vacation homes, hotels and resorts. Thus, in Indiaroba and Jandaíra, externalinterests,verticalizations, introduceorplan to implementnew projects andnewformsbased on theirinterests and logicand on suchprocesses new spaces and new territorialities are formed. Therefore, theadmission of a territorial and economicreconfiguration of Indiaroba and Jandairaisprocessedfrominternaldynamics orhorizons, endogenous to society, and vertical orexternalmovements to society, producingdifferentiatedspaces. The research investigationprocesswasdonewiththefollowingmethodological procedures: bibliographic, documentary, cartographicand field research. The presentthesishad as objective to analyzethehorizontalities and verticalities in the territorial and economicreconfiguration of Indiaroba and Jandaíra. Consideringthefollowingscenario, thequalitative approach proved to bethemostsuitableto interpretthisphenomenon. Indiaroba and Jandaíramunicipalitieshavebeenapproved, they still have a rareoccupation, with some settlementsthat still remain "invisible" and poorlyintegrated as capitals, remaining as peripheralspaces, such as "borders" or "territorial funds". Horizontalitiesexpresstheaims and dynamics of local societies and help developmechanisms of aggregation and solidaritybetween Indiaroba and Jandaíra. Bothgenerate a cohesion of local society and a process of decision-makingautonomywhichis a form of resistance to territorial and economicreconfigurationin whichtheyare goingthrough to attenddemands of the global market. Suchreconfigurationsweredriven by verticalities, whichrefer to global and social intereststhat determine as internalmodalitiestheactions and attend to theinterests ofthehegemonicgroups, oftenunderminingthe local solidaritiescreated by horizontality and leading to conflicts.